Biodegradation of Plastic Waste: Environmental Implications and Remediation Approaches - Mr. Bhagawt R. Gurme (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Microplastics, defined as plastic particles less than 5 mm in size, have become a pervasive environmental pollutant, threatening ecosystems and human health. This review paper explores the chemistry of microplastics, focusing on their degradation pathways, environmental behavior, and ecological impacts. The study examines the physical, chemical, and biological degradation mechanisms of microplastics, including photodegradation, hydrolysis, and microbial degradation, and their role in the generation of secondary pollutants. Additionally, the paper discusses the environmental distribution, toxicity, and bioaccumulation of microplastics in aquatic and terrestrial ecosystems. Emerging mitigation strategies, such as advanced oxidation processes, enzymatic degradation, and biodegradable alternatives, are also reviewed. By synthesizing recent research, this paper aims to provide a comprehensive understanding of microplastic pollution and guide future efforts toward sustainable solutions.
Keywords: Plastic Waste; Biodegradation Mechanisms; Ecological Effects; UV-Induced Degradation; Polymer Hydrolysis; Microbial Enzymes; Oxidative Remediation; Plastic-Degrading Bacteria; Biopolymer Substitutes; Bioaccumulation Hazards; Solid Waste Management; Microbial Metabolites; Environmental Contaminants; Green Remediation; Biodiversity Impact; Toxic Exposure; Polystyrene (PS); Polyvinyl Chloride (PVC); Waste Reduction Strategies; Eco-Innovative Technologies